Implementation of the Sheep Investment Program Innovation in Suco Village, Mumbulsari District, Jember Regency - Firra Septianti Ananditya; Putri Robiatul Adawiyah (Empat Sembilan Publisher, 2026)
This study aims to describe the implementation of the Sheep Investment Tourism Program in Suco Village as an innovative economic development initiative based on local potential. The program integrates community investment, sheep farming, and educational tourism to improve the welfare of rural communities. The research focuses on investment management, the organization of farmer groups, livestock management, and the profit-sharing system. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and were analyzed interpretively to examine the program's implementation process as well as its supporting and inhibiting factors. The findings indicate that the Sheep Investment Tourism Program has contributed to community empowerment and the strengthening of the village economy through collaboration among the village government, farmer groups, and community members as investors. However, the program continues to face challenges related to management transparency, managerial capacity, and long-term sustainability. Therefore, strengthening the management system and enhancing accountability are essential to ensure the program's sustainable development.